Proteins marking the sequence of genotoxic signaling from irradiated mesenchymal stromal cells to CD34+ cells - Samra, Vanessa; Drews, Oliver; Costina, Victor; Bierbaum, Miriam; Jawhar, Ahmed; Röhl, Henning; Weiß, Christel; Brendel, Susanne; Kleiner, Helga; Flach, Johanna; Spiess, Birgit; Seifarth, Wolfgang; et al. (International journal of molecular sciences, 2021)
Non-targeted effects (NTE) of ionizing radiation may initiate myeloid neoplasms (MN). Here, protein mediators (I) in irradiated human mesenchymal stromal cells (MSC) as the NTE source, (II) in MSC conditioned supernatant and (III) in human bone marrow CD34+ cells undergoing genotoxic NTE were investigated. Healthy sublethal irradiated MSC showed significantly increased levels of reactive oxygen species. These cells responded by increasing intracellular abundance of proteins involved in proteasomal degradation, protein translation, cytoskeleton dynamics, nucleocytoplasmic shuttling, and those with antioxidant activity. Among the increased proteins were THY1 and GNA11/14, which are signaling proteins with hitherto unknown functions in the radiation response and NTE. In the corresponding MSC conditioned medium, the three chaperones GRP78, CALR, and PDIA3 were increased. Together with GPI, these were the only four altered proteins, which were associated with the observed genotoxic NTE. Healthy CD34+ cells cultured in MSC conditioned medium suffered from more than a six-fold increase in γH2AX focal staining, indicative for DNA double-strand breaks, as well as numerical and structural chromosomal aberrations within three days. At this stage, five proteins were altered, among them IQGAP1, HMGB1, and PA2G4, which are involved in malign development. In summary, our data provide novel insights into three sequential steps of genotoxic signaling from irradiated MSC to CD34+ cells, implicating that induced NTE might initiate the development of MN.
Gesehen am 11.10.2021